A escolarização de alunos com deficiência mental incluídos nas séries finais do ensino fundamental: um estudo das expectativas das famílias - Duarte, Jaluza de Souza (2008)
This dissertation brings as a theme Schooling of mentally disable students included into the final grades of Elementary School: a study about families expectations . Four families with mental disable students participated in the research. These students are included into the final grades of Elementary School in a State School of Santa Maria city. The work is composed by a descriptive research with a qualitative interpretation and characteristic of case study. Semistructured interview was used as a technique to collect data. The interviews were answered by the students mothers. This work had as an objective to investigate the schooling expectations for the families with mentally disable children; besides comprehending the family processes of school mobilization, revealing the families routines that demonstrate to be in favor of their mentally disable children s schooling process. The obtained data from the interviews were organized into three sections of this work, with an approximation of these information with theoretical elements that based the analyses. In the data comprehension, several topics emerged to be discussed, reaffirming the families importance in their children s schooling process. The content presented in the speeches evidence that all the families attribute an important symbolic value to the school. However, in relation to these families expectations with schooling, there are some elements that indicate singularities referred to what they expect from schooling. It is possible to perceive that the singularity is also present in the way the families move on to their children s schooling process and that does not occur isolated, but is supported by the school where the children study. Among the families routines that revealed being in favor of schooling, (more effective in determined families) are: the effective support to inclusion; school involvement; the relation with teachers; determination to the permanence of a domestic moral order; vigilance and attention to the school work. In the comprehension of this process, it is necessary to evidence that some factors influence in the way the families perceive and invest in their children s education. In the case of this research, besides economical, social and cultural factors, it is necessary to consider situations brought by the child s disability, however these factors can not be seen isolated, but in their interdependent relations. Besides revealing the families relation to the children s schooling process, the research shows that the families need financial, material, emotional, symbolic and informative support so that they can contribute in a positive way in the schooling inclusion. The smaller the family s cultural level is, the more necessary this support is. The families also need more opportunities to their mental disable children, not only in their childhood, but also in their adolescence and adult age. The necessity of the school search for a more effective work with the families is also highlighted, so that they can carry out together a school life planning of the students.